IKiS Self Service Kiosk for Library Service - -, Mardiana; Muhammad, Meizano Ardhi (Prosiding International conference on Information Technology and Business (ICITB), 2017)
Institutional Repository (IR) Digital Collections in Unila Library is a restricted access collection, it is not directly accessible for users. Transactions such as whole collection information retrieval, printing and payment can be made only through librarians. Sometimes it leads to slow services due to the number of transaction requests queues from users. There were no system or device such as Kiosk that can be used independently for such purposes to minimize or even eliminate queue for librarians. Purpose of this research is to develop a KiosK self-contained system called Interactive Kiosk System (IKiS). IKiS serves for searching, accessing information as well as for self-printing transactions in Unila Library. IKiS hardware development uses hardware interface for input (barcode reader) and output (printer). IKiS casing made in accordance with the size and layout of the device as well as considering user ergonomics. Prototype method used for software development which focuses on functionality and user ergonomic. Data source retrieved from existing system data library which are IR collection on Eprints, ebook collection and ejournal collection on SLiMS. API (Application Programming Interface) is developed for transaction between data source to IKiS software. Testing is done on hardware, software, and both as a whole unit. Based on the test results, IKiS Print Mandiri can work well and meet the functionality required by Unila library. The research succeeded in realizing KiosKs self-service printing system tested on IR Library collection users of Unila Library. Use of the Web Service API and common computer tools make IKiS Independent Print agnostic against the IR Digital Collection system. This provides an opportunity for adoption on a wider scale as an improvement of services in the Library in general.Keyword: Index Termsâe-Kiosk, Institutional Repository, Library Services, Self-service Printing